Formação de grãos ferríticos ultrafinos através de transformação de fase induzida por deformação - Ferracini Junior, Elcio Geraldo (2007)
One of the key points in steel development has been the refinement of the microstructure, however without change the chemical composition with addition of alloy elements. The refinement of the ferrite grain size leads simultaneously to an increase in strength and toughness. Ultrafine grains can be produced through thermomechanical controlled treatments, generated by dynamic strain-induced phase transformation (g®a), which also can be associated with others dynamic phenomena, such as dynamic recrystallization. In this work a low and a middle carbon steel were previously austenitized at 900ºC for 180 s and cooled at 1ºC/s to a given deformation temperature established in relation to their critical temperatures. The deformation were applied with a strain of 2,5 at a strain rate of 1 s-1. The behavior of the materials during the deformation was analyzed using the stress-strain curves obtained from torsion experiments. After deformation, the samples were air cooled and the final microstructure characterized by scanning electron microscopy. It was determined with success a route capable to produce ultrafine ferrite grains, where grain size of 1,6 μm were produced for the Cos Ar 60 steel and 1,3 μm for the SAE 1548 steel.